Determination of creep parameters in layers of building composites/Sluoksniuotųjų statybinių kompozitų valkšnumo parametrų nustatymas - Marčiukaitis, Gediminas (Journal of Civil Engineering and Management, 1998)
Various composite building products consisting of layers of different physical-mechanical properties being tied rigidly together are manufactured and used in construction. In many cases such products curve, become flaky, crack and their thermo-insulating capability suffers. It occurs because deformation properties are not adjusted, different layers of such products deform differently under the load. And the deformation effects the behaviour of the whole structure. A correct adjustment of deformations can be achieved with allowance for creep of different layers and of the whole composite. Determination of creep parameters – creep coefficient and specific creep – depends on the orientation of layers in respect of the direction of force action. When layers are situated transverselly in respect of the direction of action of forces (stresses), creep parameters of composite depend on creep parameters of materials of separate layers and on relative volumes of these layers. Creep deformations of a composite can be described by equations describing creep of individual layers. Appropriate equations and formulas (17)–(25) are presented for determining such deformations. When layers are parallel to the direction of stresses, redistribution of these stresses between layers takes place. Compression stresses increase in a layer with higher modulus of deformation and decrease in that with lower modules. Proposed equations (37)–(42) enable to determine redistribution of stresses between layers, the main creep parameters of composite, their modulus of deformations and creep deformations themselves when strength of a composite product is reached, E(t0) = E(t) = const and stresses produce linear creep. Such loading of a composite product is the most common in practice. Presented formulas ((46), (52)) and diagrams show that it is possible to design a composite building product or material with creep parameters given in advance by means of appropriate distribution of product layers, selecting ratios between layers and properties of materials.Article in Lithuanian.First Published Online: 26 Jul 2012